2019
DOI: 10.1002/ppul.24292
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal asthma is affected by genetic interactions between RORA and NPSR1

Abstract: Background Neuropeptide S Receptor 1 ( NPSR1) and Retinoid Acid Receptor‐Related Orphan Receptor Alpha (RORA ) interact biologically, are both known candidate genes for asthma, and are involved in controlling circadian rhythm. Thus, we assessed (1) whether interactions between RORA and NPSR1 specifically affect the nocturnal asthma phenotype and (2) how this may differ from other asthma phenotypes. Methods Interaction effects between 24 single‐nucleotide polymorphisms (SNPs) in RORA and 35 SNPs in NPSR1 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Several other genes included in the models were not connected to the ICS response mechanisms per se, but have been linked to asthma severity, asthma control, airway remodeling, and Th2-mediated responses. ABCA7 gene expression is associated with nocturnal asthma symptoms in individuals with a polymorphism in NPSR1 [ 43 ]. BSG (also called CD147 ) is a potential target for asthma treatment therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several other genes included in the models were not connected to the ICS response mechanisms per se, but have been linked to asthma severity, asthma control, airway remodeling, and Th2-mediated responses. ABCA7 gene expression is associated with nocturnal asthma symptoms in individuals with a polymorphism in NPSR1 [ 43 ]. BSG (also called CD147 ) is a potential target for asthma treatment therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid receptor related orphan receptor alpha (RORA) and Neuropeptide S receptor 1 (NPSR1) are potential asthma genes that have recently been shown to regulate circadian rhythm. Using large cohorts from previous asthma studies, Gartner et al 9 found that interactions between RORA and NPSR1 SNPs were strongly associated with nocturnal asthma rather than strictly asthma in general. Limitations include questionnaire‐based definition of nocturnal asthma and the fact that this was a retrospective study.…”
Section: Year In Review: Asthmamentioning
confidence: 99%